2017
DOI: 10.1016/j.engstruct.2017.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of concrete-encased concrete-filled FRP tube (CCFT) columns under axial compression

Abstract: A new composite column named concrete-encased concrete-filled fibre reinforced polymer tube (CCFT) column has been proposed in this study. This composite column consists of an inner concrete-filled fibre reinforced polymer (FRP) tube, outer concrete confined with polymer grid, and concrete cover. In this study, a total of 16 concrete stub columns were cast and tested under axial compression. Columns were divided into eight groups, which included one group of plain concrete columns, two groups of FRP confined c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Results indicated that significant increase in strength and ductility of concrete can be achieved by FRP composite jackets. Wang et al [14] conducted 16 FRP confined concrete stub column and found that by increasing the concrete strength, the peak load of column can be increased. Vincent et al [15] investigated the effect of fiber angle on axial compressive behavior of circular FRP confined concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that significant increase in strength and ductility of concrete can be achieved by FRP composite jackets. Wang et al [14] conducted 16 FRP confined concrete stub column and found that by increasing the concrete strength, the peak load of column can be increased. Vincent et al [15] investigated the effect of fiber angle on axial compressive behavior of circular FRP confined concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages of high strength and stiffness to weight ratios as well as superior corrosion resistance, fibre reinforced polymer (FRP) has been extensively used in recent years to improve the compressive, flexural, and shear behaviours of concrete members [1][2][3][4][5][6]. One popular application of FRP is to provide confinement to concrete columns [7][8][9][10][11][12][13][14][15]. Both experimental and analytical studies have proven that the FRP confinement can enhance the strength and ductility of concrete under compressive loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies have proven that FRP wrapping of RC columns is an effective means of enhancing their strength and ductility as it provides confinement to the concrete core (Ozbakkaloglu and Oehlers, 2008;Moshiri et al, 2015;Vincent and Ozbakkaloglu, 2014;Mirmiran et al, 1998;Pessiki et al, 2001;Chaallal et al, 2003;Chaallal et al, 2000;Sezen and Miller, 2011;Ilki et al, 2008;Alecci et al, 2014;Ilki and Kumbasar, 2003;Wang et al, 2017;Sheikh et al, 2007;Silva and Rodrigues, 2006;Cui and Sheikh, 2010b;Masia et al, 2004;Lam and Teng, 2004;Matthys, 2000;Parghi and Alam, 2018).…”
mentioning
confidence: 99%